Eco pedagogic Based on Local Wisdom as an Effort to Grow Students’ Ecological Awareness - Zahrawati, Fawziah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
Ecological awareness is an awareness that is important for someone to have as an effort to solve the problem of environmental crisis. This study aims to determine the portrait of students’ ecological awareness, the use of eco-pedagogy based on local wisdom to foster students’ ecological awareness, and the challenges faced by teachers in growing students’ ecological awareness. This research is a qualitative research conducted at SDN 16 Sayowang. Informants are school principals, teachers, staff, and students selected by purposive sampling. To obtain data interviewed, observation, and documentation. The validity of the data was obtained through triangulation of theories, methods, and sources. Next, the data is analyzed. This study found that the portrait of students’ ecological awareness can be seen from the ability to distinguish between organic and inorganic waste. Using local wisdom-based eco-pedagogy is carried out by utilizing school culture and through the learning process. The teacher takes as an example the traditions carried out by the local community and are related to the value of loving the environment, such as the appadekko tradition. To raise ecological awareness, it cannot be separated from the challenges faced by teachers, namely students who have diverse family backgrounds, students who have a diversity of characteristics and learning styles, as well as the influence of student association in society. The findings of this study can be an example of the use of local wisdom in instilling the value of loving the environment in students.